Design of transceivers based on sparse Bayesian learning for power line carrier communications - Xinrong LV; Youming LI; Mingchen YU (Dianxin kexue)
Aiming at the problem of the influence of multipath channel and impulse noise on the performance of power line carrier communication system,a transceiver scheme for power line communication system was proposed which could effectively combat the influence of multipath channel and impulse noise.Firstly,the power line channel impulse response and the impulsive noise in the time domain were jointly viewed as a sparse vector.Then,the sparse Bayesian learning theory was adopted to estimate the power line channel and impulse noise jointly.The impulse noise was removed and the channel gain was compensated at the receiver.The simulation result shows that the proposed receiver scheme has better performance than traditional receiver considering channel estimation and impulse noise suppression separately.